Assessing Port Governance, Devolution and Terminal Performance in Nigeria - D. E. Onwuegbuchunam (Logistics, 2018)
Concerns about performance and efficiency in port terminals led many national governments to embark on port reforms. The Federal government of Nigeria, for example, adopted the Landlord port model which brought about concessioning of port terminals to private operators. Despite high investments in terminal facilities by the private terminal operators, there are still complaints about level of service offered to port users. This paper applied key performance indicator metrics and parameters of queuing model in assessing performance of Nigeria’s concessioned port terminals. Data for the study were obtained from terminal level records of cargo and ship handling activities for years 2000 to 2015. Major findings indicate that cargo and vessel throughputs improved after the reforms in the six ports examined. However, much variability was observed in trends in ships’ turnround times across all ports after the concession policy implementation. Additional results from the queuing model analysis suggest that the high ships turnround times observed in some ports are associated to delays in ship operation at the berths. The paper recommends that policy interventions be focused on ship operations at the berths as a step in improving service level in the port terminals.